PENGARUH PERLAKUAN HIPOTERMIA RINGAN PADA KASUS CEDERA OTAK AKIBAT TRAUMA RISIKO TINGGI BERDASARKAN GLASGOW COMA SCALE DAN KADAR PROTEIN TNF-Î± - Hendratno, Josep; Prasetyo, Eko; Oley, Maximillian Ch. (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Mild hypothermia treatment could be a useful method for improving the outcome of neurological treatment in patients with severe traumatic brain injury (TBI). There are several mechanisms underlying this effect inter alia reduction of metabolic rate, attenuation of excitatory amino acid and free radical synthesis, suppression of inflammatory responses, and prevention of blood-brain barrier disruption and brain edema. This study was aimed to obtain the effect of mild hypothermia treatment on Glasgow Coma Scale (GCS) dan TNF-? level among patients with severe TBI. This was an experimental analytical study. Subjects were adults aged 16-45 years, divided randomly into two groups (mild hypothermia and control groups) which were observed within 24 and 72 hours. TNF-? serum level was estimated by using TNF-? in vitro simple step ELISA. The assessments of outcomes were determined by using Glasgow Coma Scale (GCS) during the mild hypothermia therapy. The results showed that there were 20 TBI patients enrolled in this study, divided randomly into two groups. The treatment group, treated with mild therapeutic hypothermia, showed a decrease in TNF-? serum level and improved clinical value of GCS score (P <0.05). Conclusion: Mild hypothermia could significantly improve the GCS score and decrease TNF-? serum level among patients with severe TBI.Keywords: mild hypothermia treatment, TNF-?, GCS score,TBIAbstrak: Terapi hipotermia ringan (HPTr) dapat memperbaiki hasil pengobatan neurologik pada pasien dengan cedera otak traumatik (COT) risiko tinggi. Beberapa mekanisme yang mendasari efek tersebut ialah antara lain pengurangan tingkat metabolisme, atenuasi asam amino rangsang maupun sintesis radikal bebas, penekanan respons inflamasi, dan pencegahan gangguan sawar darah otak serta edema otak. Penelitian ini bertujuan untuk mengetahui pengaruh perlakuan HPTr pada kasus COT risiko tinggi berdasarkan skor Glasgow Coma Scale (GCS) dan kadar TNF-?. Jenis penelitian ialah analisis eksperimental. Subjek ialah orang dewasa berusia 16-45 tahun, diacak menjadi dua kelompok yaitu kelompok perlakuan HPTr dan kelompok kontrol. Pengamatan subjek dilakukan pada 24 jam dan 72 jam. Kadar serum TNF-? diperoleh dengan menggunakan metode TNF-? in vitro simple step ELISA. Penilaian klinis dilakukan dengan mengunakan skor GCS pada 24 dan 72 jam perlakuan HPTr. Hasil penelitian mendapatkan 20 penderita COT, dibagi menjadi dua kelompok secara acak. Kelompok perlakuan HPTr menunjukkan kecenderungan penurunan kadar TNF-? serum dan perbaikan nilai klinis dinilai dengan skor GCS (P <0,05). Simpulan: Pada penderita dengan cedera otak traumatik risiko tinggi, terapi hipotermia ringan dapat meningkatkan nilai klinis skor GCS dan menurunkan kadar TNF-? serum secara bermakna.Kata kunci: hipotermia ringan, TNF-?, skor GCS, COT